Os efeitos da modalidade pregão na execução dos contratos continuados: um estudo de caso - Amorim, Patricia Carneiro Leão de (2012)
This work investigates the impact of lowest price bids made through the system of electronic reverse auctions, as seen in the performance and execution of continuous contracts negotiated by the Superintendency of Adminstration for the Advocacia Geral da União (AGU) in Pernambuco, Brazil, during the period between 2006 and 2010. The research was based on the premise that contracting lowest price bidders can stimulate a dip in prices offered by other bidders, leading to contracts with extremely low values that negatively affect the performance of services. Such contracts may be rife with problems and reduce the overall life span of continuous contracts. These apparent savings, a result of intense competition characteristic to the bidding manner of reverse auctions, should be questioned. The results of this study confirm this premise, showing that 55% of contracts generated through the electronic bidding system have serious issues, and 31% of these contracts resulted in a unilateral termination for breach of contractual terms. An inverse relationship between the initial savings generated in the bidding and contract expiration time was identified - the greater the difference between the estimated value and that which was negotiated during the bidding process, the shorter the duration of the contract. Therefore, hiring well below the market price generates contracts with short lifespans and many problems. Data analyses indicate a need to relativize the adoption of the reverse auction bidding system and reconsider its implications for continuous, effective services.